Evaluation of the hepatoprotective effects of curcumin and nanocurcumin against paraquat‐induced liver injury in rats: Modulation of oxidative stress and Nrf2 pathway. Issue 5 (5th February 2021) - Kheiripour, Nejat; Plarak, Alireza; Heshmati, Ali; Asl, Sara Soleimani; Mehri, Fereshteh; Ebadollahi‐Natanzi, Alireza; Ranjbar, Akram; Hosseini, Asieh
Abstract: Paraquat (PQ) is a widely used herbicide all over the world, which is highly toxic for animals and humans. Its cytotoxicity is based on reactive radical generation. The aim of this study is to evaluate and compare the hepatoprotective effects of curcumin and nanocurcumin against liver damage caused by sub‐acute exposure with PQ via modulation of oxidative stress and genes expression of nuclear factor erythroid 2‐related factor 2 (Nrf2) pathway. Rats were exposed to PQ (5 mg/kg/day, orally) + curcumin or nanocurcumin (100 mg/kg/day, orally) for 7 days. Then rats were anesthetized and serum and liver samples were collected. Next, serum enzymatic activities, liver histopathology, oxidative stress, and expression of genes involved in Nrf2 signaling pathway were assessed by biochemical and enzyme‐linked immunosorbent assay methods, hematoxylin and eosin staining, and real‐time polymerase chain reaction analysis. PQ significantly increased malondialdehyde, alanine transaminase, aspartate aminotransferase, alkaline phosphatase levels, and Kelch‐like ECH‐associated protein 1 gene expression and also decreased total antioxidant capacity, total thiol group levels, Glutathione S‐transferases, heme oxygenase 1, Nrf2, and NAD(P)H:quinone oxidoreductase 1 genes expression, causing histological damages to liver tissue. These changes were significantly modulated by curcumin and nanocurcumin treatments. Our findings showed that nanocurcumin had better hepatoprotective effect than curcumin in liver damage after PQ exposure most likely through modulation of oxidative stress and genes expression of Nrf2 pathway.